1991
DOI: 10.1007/bf01297021
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in children with peptic ulcer and their families

Abstract: Little is known about the source and spread of Helicobacter pylori, but transmission from infected family contacts has been suggested. We have therefore investigated 15 children with peptic ulcer and their first-degree relatives for H. pylori. Serum anti-H. pylori IgG, pepsinogen I, and gastrin levels were measured. Endoscopy was carried out on the children and relatives, and biopsies were taken from the gastric antrum for histology, microbiology, and urease testing. Six of 11 children with duodenal ulcer (55%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 18 publications
5
45
1
3
Order By: Relevance
“…Previous investigations using serological or histological diagnosis and/or the [ 13 C]urea breath test have demonstrated an intrafamilial clustering of H. pylori infections in Canada (8), the United States (18), Italy (7,27), and England (1,26). It has also been suggested that H. pylori is transmitted from infected parents, especially infected mothers, to children in Germany (4,28,29), the United States (10), and Japan (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations using serological or histological diagnosis and/or the [ 13 C]urea breath test have demonstrated an intrafamilial clustering of H. pylori infections in Canada (8), the United States (18), Italy (7,27), and England (1,26). It has also been suggested that H. pylori is transmitted from infected parents, especially infected mothers, to children in Germany (4,28,29), the United States (10), and Japan (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Quando são excluídos os casos com úlcera relacionados a drogas antiinflamatórias, o H. pylori é detectado em quase todos os ulcerosos. Cinqüenta e cinco a 100% das crianças com úlcera duodenal e cerca de 40% daquelas com úlcera gástrica são infectadas 8,[19][20][21] . Das 76 crianças com úlcera duodenal por nós investigadas 69 tinham úlcera duodenal primária e, dentre elas, 83% e 91%, respectivamente, eram H. pylori positivas.…”
Section: Fatores Ambientaisunclassified
“…6 Peptic ulcers also occur in H. pylori-negative patients, especially those receiving nonsteroidal anti-inflammatory drugs (nSaids), as shown in other studies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] in a previous uncontrolled study, 1 we assessed the frequency of gastro-duodenal ulcers/erosions in dyspeptic children referred for upper gastrointestinal (gi) endoscopy in 14 european countries. ulcers and/or erosions were observed in 56 of 694 children (8.1%).…”
mentioning
confidence: 99%